The Educational Challenge of Unraveling the Fantasies of Ontological Security. Issue 2 (3rd April 2017) - Stein, Sharon; Hunt, Dallas; Suša, Rene; de Oliveira Andreotti, Vanessa
ABSTRACT: In this article we address the current context of intensified racialized state securitization by tracing its roots to the naturalized colonial architectures of everyday modern life—which we present through the metaphor of "the house modernity built." While contemporary crises are often perceived to derive from external threats to the house, we argue that in fact these crises are a product of the violent and unsustainable practices that are required in order to build and sustain the house itself. As the structural integrity of the house increasingly comes under strain, there are different possible responses, three of which we review here. We conclude by asking what kind of education might enable us to imagine and practice alternative formations of existence in a context where the house appears to be crumbling, and, indeed, has always been a fantasy.